Ritual dalam adat tepung tawar perkahwinan masyarakat melayu Sarawak di Petra Jaya, Kuching, Malaysia - Bohari, Sarra Jesstika (2020)
This study related to the implementation of "Tepung Tawar" ritual in marriage customs of Sarawak Malay society in Petra Jaya, Kuching. The Sarawak Malay community of "Tepung Tawar" tradition has its own uniqueness and is quite different from others. There are two main research objectives which are to identify processes and materials involved, as well as to analyse the meaning of symbols in this customary implementation. The investigation used was ethnographic method. The data collection techniques used in this study consist of depth interview with custom practitioners as primary resource and several respondents selected based on field studies conducted. In addition, the observation method was also carried out to review the process before and during the ritual of "Tepung Tawar" customary in the wedding. The location of the study selected is Petra Jaya area in Kuching because it is the original settlement of the Malay community in Sarawak. The findings found that there are two processes involved in this customary implementation which is the process of preparation of materials and equipment as well as the implementation procedure for "Tepung Tawar" rituals. This customary is seen in the application of living values through symbolic interaction during "Tepung Tawar" exercise. Even the value of life of the Malay community is based on Islamic guidance, but they still continue to observe the customs of the past generations by making some reformations based on Islamic religious teachings. The comprehension of ritual exercise is to ensure the well-being of the practiced community established on the purity and teachings of Islam. It is translated in their lives through incorporating prayers and Islamic values in order to fill the gap in the culture of Melayu Sarawak community. The Purity Symbol Model (2012) adopted in this study has helped in analysing the meaning of symbols in the custom "Tepung Tawar'' rituals of the Sarawak Malay wedding. The symbolic value in this ritual emphasise on the concept of purity indirectly has bonded the group's community by placing that every act to be taken must be accompanied by good intention. Hence, the ritual in this tradition preserve harmony within the family institution and members of the practiced community.